Controlled human malaria infection: overview and potential application in the evaluation of transmission-blocking interventions in malaria-endemic areas - Enock J. Kessy; Ally I. Olotu (Malaria Journal)
Abstract Controlled human malaria infection (CHMI) involves the intentional infection of healthy individuals with malaria parasites, close observation of the volunteers, and clearance of the parasite at a predetermined endpoint. Depending on the need, CHMI can be initiated by either sporozoites or the administration of parasite-infected erythrocytes, with each of the two systems offering different advantages and caveats. Among other uses, CHMI has proven to be a useful tool for the evaluation of new malaria interventions, particularly vaccines and drugs. The majority of CHMI studies have been conducted in Europe, the USA and Australia, with only a handful of studies conducted in malaria-endemic countries. The slow adoption of CHMI in malaria-endemic countries may be attributed to a lack of infrastructure and expertise to conduct studies in malaria-endemic countries and the risk of undue influence and coercion as a result of volunteers' vulnerability due to a lack of education and financial situation. With the need to generate results relevant to the target populations, there has recently been an increase in CHMI studies that are being conducted in malaria-endemic countries. The use of CHMI models for the evaluation of preerythrocytic and blood-stage malaria interventions has been attempted in malaria-endemic countries with great success. There is a need for the adoption of a CHMI model for the evaluation of transmission-blocking interventions in malaria-endemic countries. The establishment of such a model in malaria-endemic countries will facilitate the selection of potential transmission-blocking intervention (TBI) candidates and accelerate their development. Here is an overview of CHMI, key challenges and ethical considerations in adopting CHMI for the evaluation of malaria transmission-blocking interventions in malaria-endemic countries.